Pemulihan Psikologis Anak Korban Kekerasan Seksual di Indonesia: Pendekatan Perlindungan Hukum - M. Yusuf; Irwan Effendi; Firda Laily Mufid (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2026)
Sexual violence against children remains a frequent occurrence in Indonesia; whilst the examination of cases involving children as victims is essential, it is influenced by psychological factors. This study aims to analyse the forms of legal protection for children as victim-witnesses through a psychological lens. In this study, the author will employ an empirical legal research method. Empirical research is a legal research method designed to examine the law in its practical application and to investigate how the law functions within society. The data analysis method employed in this study is descriptive analysis, which involves analysing data from the literature by explaining the results or realities in a logically structured manner. The findings of this study indicate that legal protection for children as victim-witnesses in cases of sexual violence forms part of the rights enshrined in the constitution. This protection is based on various legal provisions, such as those in the Criminal Code and Law No. 35 of 2014 on Child Protection. To reinforce this, Indonesia ratified the United Nations Convention on the Rights of the Child of 1989 through Presidential Decree No. 39 of 1990 to strengthen children’s right to protection. From a psychological perspective, recovery is oriented towards fulfilling children’s rights following sexual violence. The fulfilment of victims’ rights in the handling of sexual violence cases is set out in Article 67 of the TPKS Law, which states that the rights of victims of sexual violence consist of the right to Handling, the right to Protection, and the right to Recovery.